MySmartE – An eco-feedback and gaming platform to promote energy conserving thermostat-adjustment behaviors in multi-unit residential buildings. (1st August 2022) - Kim, Huijeong; Ham, Sangwoo; Promann, Marlen; Devarapalli, Hemanth; Bihani, Geetanjali; Ringenberg, Tatiana; Kwarteng, Vanessa; Bilionis, Ilias; Braun, James E.; Rayz, Julia Taylor; Raymond, Leigh; Reimer, Torsten; et al.
Abstract: In this paper, we present a first-time cloud-based eco-feedback and gaming platform that aims to promote energy conserving thermostat-adjustment behaviors in multi-unit residential buildings. To achieve this goal, we introduce a new modeling approach for personalized eco-feedback design integrated with a collaborative social game to assist residents enhance their thermostat use while promoting community-level energy savings. Our modeling framework is integrated into a cloud-based application, MySmartE, with visual (wall-mounted tablet) and voice (Alexa) user interfaces to facilitate behavioral changes in a user-centric approach. The platform is deployed in a multi-unit residential community in Fort Wayne, IN, and data from the field study are used to investigate: (i) how occupants' thermostat behaviors changed after using the MySmartE app; (ii) how users interacted with the app during the game; and (iii) how was users' experience with the developed platform. Despite the heterogeneous characteristics of households, the results from the field study showed the positive effect of the intervention in the thermostat-adjustment behaviors, which resulted in an increase in the indoor temperature during the cooling season compared to the baseline. Findings from the user interaction analysis and post-experiment interviews also revealed the significant potential to nudge households' energy conservation behaviors with the developed platform along with the challenges that should be tackled to derive long-term behavior changes. Highlights: Presented a smart eco-feedback and gaming platform that aims to promote energy conserving thermostat-adjustment behaviors. Introduced a new modeling approach for personalized eco-feedback design integrated with a collaborative social game. Developed visual and voice user interfaces to facilitate behavioral changes in a user-centric approach. Deployed the developed platform in a multi-unit residential community. Conducted a field study to evaluate the effect of the platform on occupant behavior.